Study of Decapod Diversity and Habitat in the Coastal Line Area of Bengkulu City Beach - Chairunisa, Aprilia; Primair Yani, Ariefa; Parlindungan , Deni; Nursa'adah, Euis; Defianti, Aprina; Karyadi , Bhakti (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to identify abundance, species diversity, dominance, and evenness and to determine the type of decapod habitat on the coast of Bengkulu City. The method used is the survey method. The sampling location was divided into three stations: Pasir Putih Beach, Panjang Beach, and Kualo Beach. The sampling technique used transects, at each station, an area of 300 m was taken. Decapod diversity was analyzed using the Shannon-Wiener formula, the dominance index (C) was analyzed using Simpson's dominance index, and the evenness index was calculated using Pielou. The results of the research show that on the coast of Bengkulu City, decapod species consisting of six families were found. The diversity index shows that at stations I (0.864/low), II (1.00/medium), and III (0.372/low). Dominance index at stations I (0.046/low), II (0.113/low), and III (0.003/low). Evenness index at stations I (0.415/height), II (0.466/height), and station III (0.92/height). The most common decapods found are the family Hippidae and the species Emerita emeritus, with a total of 18 individuals. The decapod habitat type on Bengkulu City Beach is a sandy beach type. Environmental parameters (DO, water pH, air humidity, light intensity, salinity, and temperature) are in conditions suitable for decapod life.